UPAYA PENINGKATAN KOMPETENSI PEDAGOGIK GURU IPS MELALUI KEGIATAN MGMP DI SMPN 16 PEKANBARU - Mido Emero; Bedriati Ibrahim; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Teachers as educators responsible bequeath values and norms tosubsequent generations. Education plays a very important in the process of improvingthe quality of human resources. Improving the quality of education is a process that isintegrated with the process of improving the quality of human resources. Recognizingthe importance of the process of improving the quality of human resources, thegovernment together with the private sector together to work to make education inIndonesia more qualified among others, through the development and improvement ofcurriculum and evaluation system, improvement of educational facilities, developmentand procurement of teaching materials, and training for teachers and other educationpersonnel. The purpose of this study was to determine the pedagogical competence ofteachers IPS in activities MGMP in SMP 16 Pekanbaru, to know the difficulties incarrying out the activities in MGMP, for mengtahui effort must be made to overcomethe difficulties in conducting in MGMP, and to determine the relationship MGMP theachievement of a good teacher pedagogical competence. The method used in this studyis a qualitative and descriptive analysis. Data obtained from questionnaires andinterviews were analyzed by using percentage calculations. The research location is inSMP 16 Pekanbaru. When the study began seminar proposal to the thesis examination.The data collection technique used is the technique of questionnaires, interviews, anddocumentation and tabulation of the data contained in the form of a frequency table. Inthis study as a benchmark efforts to improve teachers' pedagogical competence throughMGMP IPS in SMP 16 Pekanbaru is composed of 10 indicators. The data collected inthe questionnaire authors then analyzed, after being found last percentage isinterpreted by the sentences are qualitative. The 10 indicators are: 1). UnderstandingKareteristik Students Of Physical Aspects, Moral, Spiritual, Social, Cultural,Emotional, and Intellectual. 2). Mastering Learning Theory and Principles of LearningThe Educate. 3). Develop Curriculum Related Subjects With The Amnestied. 4). TheEducating Learning organizes. 5). Utilizing Information and CommunicationTechnology for Learning. 6). Facilitate the Development of Potential Students toactualize various potentials Owned. 7). Communicating Effectively, empathetic, andSantun With Students. 8). Conducting Assessment and Evaluation Process of Learning.9). Utilizing Assessment and Evaluation for learning needs. 10). Take Action ForImprovement Reflective Learning.Keywords: Pedagogical competence, social teachers, MGMPs activities